The Effect of Experimental-Based Problem-Based Learning on Undergraduate Students’ Scientific Writing and Presentation Skills in a Basic Physics Course - Sari, Lutfiana Ditta; Sudarti, Sudarti; Siswati, Bea Hana (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effect of experimental-based Problem-Based Learning (PBL) on students’ scientific writing and presentation skills in a Basic Physics course. Methodology: The study employed a quasi-experimental posttest-only control group design involving 73 undergraduate students from the Biology Education program. Participants were divided into an experimental group receiving experimental-based PBL instruction and a control group receiving conventional learning. Data were collected using validated rubrics for scientific writing and scientific presentation skills. Data analysis was conducted using descriptive statistics, independent samples t-tests, One-Way ANOVA, and the Mann–Whitney U test. Main Findings: The results show that students in the experimental group achieved significantly higher scientific writing scores (M = 562.97) than those in the control group (M = 518.19), with significant differences across most writing components (p < 0.05). One-Way ANOVA results indicate a very large effect size (Partial Eta Squared = 0.970). In addition, scientific presentation skills were significantly higher in the experimental group across all assessed indicators, including contribution, collaboration, confidence, content mastery, and communication (p = 0.000). Novelty/Originality of this study: This study provides empirical evidence that experimental-based PBL effectively enhances both scientific writing and presentation skills in an interdisciplinary Basic Physics learning context. The findings highlight the role of inquiry-oriented and experimental learning in strengthening scientific communication skills and offer practical implications for improving scientific literacy in higher education.